Trends in Archaeological Network Research: A Bibliometric Analysis - Brughmans, Tom (Journal of historical network research, 2017)
This paper presents an overview of major trends in archaeological network research through a bibliometric analysis of the full corpus of publications on the topic between 1965 and 2016. It illustrates we can begin identifying the outlines of a new sub-discipline within archaeology with its distinct traditions, including a diversity of research approaches, dedicated events and preferred publication venues. This sub-discipline is at a similar stage of development as historical network research, and we argue that archaeologists and historians alike interested in establishing network research as a key tool for exploring social change will have a greater chance for success to the extent that we actively collaborate, pool resources, engage in common community activities and publications, and learn from each other’s mistakes.